Trans-cultural Adaptation and Validation of the “Teacher Job Satisfaction Scale” in Arabic Language Among Sports and Physical Education Teachers (“Teacher of Physical Education Job Satisfaction Inventory”—TPEJSI): Insights for Sports, Educational, and Occupational Psychology - Chalghaf, Nasr; Guelmami, Noomen; Re, Tania Simona; Maldonado Briegas, Juan José; Garbarino, Sergio; Azaiez, Fairouz; Bragazzi, Nicola L. (Frontiers in Psychology, 2019)
Background: Job satisfaction is largely associated with organizational aspects, including improved working environments, worker’s well-being and more effective performance. There are many definitions regarding job satisfaction in the existing scholarly literature: it can be expressed as a positive emotional state, a positive impact of job-related experiences on individuals, and employees’ perceptions regarding their jobs. Aims: No reliable scales in Arabic language to assess job satisfaction in the sports and physical education field exist .This study aimed to trans-culturally adapt and validate the Pepe’s “Teacher Job Satisfaction Scale” 9 items (TJSS-9), creating the “Teacher of Physical Education Job Satisfaction Inventory” (TPEJSI) in Arabic language. This scale was administered to a Tunisian population of sports and physical education teachers and analyzed according to the Pepe’s theoretical model.. More in detail, this investigation systematically tested its factor structure, in terms of internal consistency/reliability, predictive validity, sensitivity and convergent validity. Methods: A total of 417 Tunisian teachers of sports and physical education participated voluntarily in this study. The sample comprised of 258 males and of 159 females. More in detail, 189 were teachers teaching in primary schools of physical education, 105 teaching in secondary schools, and 123 were university teachers. Both exploratory (EFA) and confirmatory (CFA) factor analyses were performed on random-split halves of the sample. Results: The three-dimensional alpha coefficients of the TPEJSI were all greater than 0.80: for satisfaction with colleagues, alpha was 0.865; for satisfaction with parents, alpha was 0.856 and for satisfaction with students alpha was 0.860. The CFA fit indices were satisfactory. Conclusions: Given the good EFA factor loadings, the CFA fit indices, the correlation matrix, the sensitivity analysis, the convergent validity and the excellent internal consistency, it can be concluded that the TPEJSI is a good psychometric tool that can be used to quantitatively assess the job satisfaction level among teachers of sports and physical education in the Arabic-speaking world.